а) 4x² - 4x - 15 < 0
D = b² - 4ac = 16 + 4*4*15 = 16 + 240 = 256
x₁ = (-b + √D) / 2a = (4 + 16) / 8 = 20 / 8 = 2,5
x₂ = (-b - √D) / 2a = (4 - 16) / 8 = -12 / 8 = -1,5
(x - 2,5)(х + 1,5) < 0
{ x < 2,5
{ x < -1,5
ответ: (-1,5; 2,5)
б) x² - 81 > 0
(x - 9)(x + 9) > 0
{ x > -9
{ x > 9
ответ: (-9; 9)
в) x² < 1,7х
x² - 1,7х < 0
х(x - 1,7) < 0
{ x < 0
{ x < 1,7
ответ: (0; 1,7)
г) x( x + 3) - 6 < 3 (x + 1)
x² + 3x - 6 - 3x - 3 < 0
x² - 9 < 0
(x - 3)(x + 3) < 0
{ x < -3
{ x < 3
ответ: (-3; 3)
Объяснение:
2х+7у=9а-53х-5у=2-2а 2х+7у=9а-5 2x = 9a - 7y -5 x = 1/2(9a - 7y - 5) подставляешь во 2-е уравнение
3*1/2(9a - 7y -5) = 2(1 - a) 9a - 7y - 5 = 2:3/2 (1-a)
9a - 7y - 5 = 4/3(1-a) 9a - 7y - 5 = 1 1/3 - 1 1/3a
-7y = 6 1 /3 - 10 1/3a -y = 1/7(6 1/3 - 10 1/3a)
y = -1/7 (6 1/3 - 10 1/3a)
Подставляем значение у в 1-е уравнение
2x + 7*(-1/7(6 1/3 - 10 1/3a)) = 9a - 5
2x - (6 1/3 - 10 1/3a)) = 9a - 5
2x = 9a - 5 + 6 1/3 - 10 1/3a 2x = 1 1/3 - 1 1/3a 2x = 1 1/3(1 - a)
x = 4/3:2(1-a) x = 2/3(1-a)
ответ: x = 2/3(1-a) ; y = -1/7 (6 1/3 - 10 1/3a)
Подробнее - на -